ChemInform Abstract: Heterogeneous Rhodium‐Catalyzed Aerobic Oxidative Dehydrogenative Cross‐Coupling: Nonsymmetrical Biaryl Amines. Issue 36 (August 2016) - Matsumoto, Kenji; Yoshida, Masahiro; Shindo, Mitsuru
Abstract: The first heterogeneously catalyzed oxidative dehydrogenative cross‐coupling of aryl amines is reported.